HUBUNGAN GENOTIPE rs 1042713 (Arg16Gly) DENGAN EFEKTIVITAS 2-AGONIS PADA PENDERITA ASMA - Sri Haryanti; Zullies Ikawati; Mustofa Mustofa; Tri Murti Andayani (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2021)
ABSTRACT To produce an effect, the agonist drug 2 will bind to the ADRB2 receptor. The effect of agonist 2 shows variation between individuals due to the presence of encoding gene polymorphisms. There are 80 ADRB2 polymorphisms, including Arg16Gly in amino acids 16. The innate ADRB2 genotype is called wildtype, whereas mutated ones is called mutant. The purpose of this study was to determine whether there was a relationship between genotype rs 1042713 (Arg16Gly) and the effectiveness of β2-agonist drugs in asthma sufferers. This study was an observational study with a cross sectional design and prospective data collection. Examination of the presence of gene polymorphisms and assessment of effe A total of 101 asthma patients who met the inclusion criteria were sorted by genome type by pharmacogenomic examination uses the Asthma Control Test (ACT) questionnaire. The results of the statistical test with chi square to determine the relationship of genome type and asthma control obtained p value 0.131. The comparison of the effectiveness of the wildtype genome is more effective than the mutant of 1.887x, and heterozygote is more effective 1,667x greater than the mutant. There is no significant relation between genotypes rs 1042713 (Arg16Gly) with effectiveness, but the possibility of clinical effectiveness is different. Keywords: Asthma, β2-agonist, ADRB2, genotype, effectiveness.